Transition to unstable oscillatory flames in porous media combustion - Yakovlev, Igor A.; Astakhov, Daniil; Zambalov, Sergey D.; Fursenko, Roman; Li, Jun; Maznoy, Anatoly (Combustion and flame)
The flames inside porous burners with low filtration velocity are prone to oscillatory behavior similar to unstable combustion in narrow channels but accompanied by complicated dynamics due to the irregular- ity of porous structure, flow field, and thermal gradient formed as a result of heat recuperation. This work is a numerical study within the framework of the pore-scale simulation approach devoted to investigat- ing the flame oscillation mechanisms and characteristics in a two-dimensional pseudo-irregular packed bed of particles generated using the Voronoi tessellation algorithm with constant pore size. The results demonstrate that unstable flame oscillations like flames with repetitive extinction and ignition (FREI) lead to the velocity pulsation in adjacent pore channels, where the stable flame fragments are exposed to the hydrodynamically-driven fluctuations. In the case of the flow rate close to the stability threshold, the flow pulses can reach a magnitude enough to shift the stable flame in the upstream quenching zone, promoting its oscillations with repetitive extinction and ignition. Results of parametric simulation with a variation of the particle diameter and flow velocity were summarized in the regime diagram revealing the transition between stable normal flame, FREI, and stable weak flame with the velocity reduction. The pulsating transitional regime was detected between the stable normal flame and the FREI. The amplitude and intensity of such pulsations increase monotonically with the flow rate reduction in a narrow range. Oscillations of the unstable flame and hydrodynamically-driven flame pulsations are similar in dynamics but different in their physical mechanisms. However, in irregularly packed beds of particles, both these phenomena unavoidably coexist and interfere significantly with each other due to the connectivity of the pore channels.